Perivascular adipose tissue‐derived stromal cells contribute to vascular remodeling during aging. Issue 4 (14th May 2019) - Pan, Xiao‐Xi; Ruan, Cheng‐Chao; Liu, Xiu‐Ying; Kong, Ling‐Ran; Ma, Yu; Wu, Qi‐Hong; Li, Hai‐Qing; Sun, Yan‐Jun; Chen, An‐Qing; Zhao, Qiang; Wu, Fang; Wang, Xiu‐Jie; et al.
Abstract: Aging is an independent risk factor for vascular diseases. Perivascular adipose tissue (PVAT), an active component of the vasculature, contributes to vascular dysfunction during aging. Identification of underlying cell types and their changes during aging may provide meaningful insights regarding the clinical relevance of aging‐related vascular diseases. Here, we take advantage of single‐cell RNA sequence to characterize the resident stromal cells in the PVAT (PVASCs) and identified different clusters between young and aged PVASCs. Bioinformatics analysis revealed decreased endothelial and brown adipogenic differentiation capacities of PVASCs during aging, which contributed to neointimal hyperplasia after perivascular delivery to ligated carotid arteries. Mechanistically, in vitro and in vivo studies both suggested that aging‐induced loss of peroxisome proliferator‐activated receptor‐γ coactivator‐1 α (PGC1α) was a key regulator of decreased brown adipogenic differentiation in senescent PVASCs. We further demonstrated the existence of human PVASCs (hPVASCs) and overexpression of PGC1α improved hPVASC delivery‐induced vascular remodeling. Our finding emphasizes that differentiation capacities of PVASCs alter during aging and loss of PGC1α in aged PVASCs contributes to vascular remodeling via decreased brown adipogenic differentiation. Abstract : Loss of peroxisome proliferator‐activated receptor‐γ coactivator‐1 α (PGC1α) in aged PVASCs showed decreased endothelial and adipogenic differentiation, especially brown adipocyte generation, which contribute to neointimal hyperplasia after injured arteries.